De Haas-van Alphen effect in 2D systems: application to mono- and bilayer graphene - Luk’yanchuk, Igor A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Generalization of Shoenberg theory of de Haas–van Alphen magnetic oscillation in 2D metals for the case of electrons with arbitrary spectrum dispersion is used to propose the way to determine the nature of charge carriers in 2D conducting systems: mono- and bilayer graphene. We analyzed the analytical expression for the oscillating susceptibility as a function of chemical potential and distinguished its characteristic features for carriers with normal parabolic and Dirac-like linear spectra that can be detected experimentally.